Intracellular Ca2+ modulation during short exposure to ischemia-mimetic factors in isolated rat ventricular myocytes - Pravdić, Danijel, anesteziolog (Array, 2009)
Summary: We investigated the effects of different ischemia-mimetic factors on intracellular Ca2+ concentration ([Ca2+]i). Ventricular myocytes were isolated from adult Wistar rats, and [Ca2+]i was measured using fluorescent indicator fluo-4 AM by confocal microscopy. Intracellular pH was measured using c5-(and-6)-carboxy SNARF-1 AM, a dual emission pH-sensitive ionophore. Myocytes were exposed to hypoxia, extracellular acidosis (pHo 6.8), Na-lactate (10 mM), or to combination of those factors for 25 min. Monitoring of [Ca2+]i using fluo-4 AM fluorescent indicator revealed that [Ca2+]i accumulation increased immediately after exposing the cells to Na-lactate and extracellular acidosis, but not during cell exposure to moderate ischemia. Increase in [Ca2+]i during Na-lactate exposure decreased to control levels at the end of exposure period at extracellular pH 7.4, but not at pH 6.8. When combined, Na-lactate and acidosis had an additive effect on [Ca2+]i increase. After removal of solutions, [Ca2+]i continued to rise only when acidosis, hypoxia, and Na-lactate were applied together. Analysis of intracellular pH revealed that treatment of cells by Na-lactate and acidosis caused intracellular acidification, while short ischemia did not significantly change intracellular pH. Our experiments suggest that increase in [Ca2+]i during short hypoxia does not occur if pHi does not fall, while extracellular acidosis is required for sustained rise in [Ca2+]i induced by Na-lactate. Comparing to the effect of Na-lactate, extracellular acidosis induced slower [Ca2+]i elevation, accompanied with slower decrease in intracellular pH. These multiple effects of hypoxia, extracellular acidosis, and Na-lactate are likely to cause [Ca2+]i accumulation after the hypoxic stress